Thoracomyoplasty in the Treatment of Empyema: Current Indications, Basic Principles, and Results - Petre Vlah-Horea Botianu; Alexandru Mihail Botianu (Pulmonary Medicine)
Empyema remains a challenge for modern medicine. Cases not amenable to lung decortication are particularly difficult to treat, requiring prolonged hospitalizations and mutilating procedures. This paper presents the current role of thoracomyoplasty procedures, which allow complete and definitive obliteration of the infected pleural space by a combination of thoracoplasty and the use of neighbourhood muscle flaps (latissimus dorsi, serratus anterior, pectoralis, rectus abdominis, omentum, etc). Recent publications show an overall rate of success of 90%, with a quick and definitive healing. Although rarely indicated in our days, this kind of procedures remain in the armamentarium of modern thoracic surgery. The importance of thoracomyoplasty derives from the fact that it may be a simple and definitive solution for complicated cases of chronic empyema not amenable to standard decortication.